Co-dependency for MET and FGFR1 in basal triple-negative breast cancers - Vanessa Y. C. Sung (Nature Portfolio, 2021)
Abstract Triple-negative breast cancer (TNBC) is a heterogeneous disease that lacks both effective patient stratification strategies and therapeutic targets. Whilst elevated levels of the MET receptor tyrosine kinase are associated with TNBCs and predict poor clinical outcome, the functional role of MET in TNBC is still poorly understood. In this study, we utilise an established Met-dependent transgenic mouse model of TNBC, human cell lines and patient-derived xenografts to investigate the role of MET in TNBC tumorigenesis. We find that in TNBCs with mesenchymal signatures, MET participates in a compensatory interplay with FGFR1 to regulate tumour-initiating cells (TICs). We demonstrate a requirement for the scaffold protein FRS2 downstream from both Met and FGFR1 and find that dual inhibition of MET and FGFR1 signalling results in TIC depletion, hindering tumour progression. Importantly, basal breast cancers that display elevated MET and FGFR1 signatures are associated with poor relapse-free survival. Our results support a role for MET and FGFR1 as potential co-targets for anti-TIC therapies in TNBC.